KEBIJAKAN KUALIFIKASI YURIDIS DALAM KETENTUAN PERATURAN PERUNDANG-UNDANGAN DI LUAR KUHP 2017-2018 (Lex Jurnalica, 2018)
AbstractJuridical qualification policy in terms of legislation during this worthy examined back/reset, because in practice the establishment (preparation/manufacturing) legislation during this time looks different variations of formulation. There's even awkward and problematic legally, but since 2004 there was already a general guidelines on the preparation of the criminal provisions in the regulations as contained in Act No. 10 of 2004, which is currently been replaced by Act No. 12 of 2011, then the problems to be discussed can be formulated as follows: how is the juridical qualification policy in terms of legislation and the CRIMINAL CODE beyond the juridical problems at the moment. which examined and in the analysis of limited 7 (go) of the special ACT outside the CRIMINAL CODE that raises problems juridis at this time i.e. include: Act No. 31/1999 jo ACT 20/2001 About criminal acts of Corruption; Act No. 9 2014 On Geothermal; Act No. 14 of 2008 About the openness of public information; Act No. 23 of 2004 on the Elimination of domestic violence; Act No. 15 of 2001 about the brand; Act No. 14 of 2001 Regarding Patents; Act No. 31 of 2000 Concerning industrial designs. Keywords : juridical qualification, policy,laws-invitation outside of the criminal code AbstrakKebijakan kualifikasi yuridis dalam ketentuan peraturan perundang-undangan selama ini layak dikaji kembali/ ulang, karena dalam praktek pembentukan (penyusunan/ pembuatan) perundang-undangan selama ini terlihat berbagai variasi perumusan. Bahkan ada yang janggal dan bermasalah secara yuridis, padahal sejak Tahun 2004 sudah ada pedoman umum tentang penyusunan ketentuan pidana dalam peraturan perundang-undangan sebagaimana dimuat dalam Undang-undang No. 10 Tahun 2004, yang saat ini sudah diganti dengan Undang-undang No. 12 Tahun 2011, maka permasalahan-permasalahan yang akan dibahas dapat dirumuskan sebagai berikut: Bagaimana kebijakan kualifikasi yuridis dalam ketentuan peraturan perundang-undangan di luar KUHP dan permasalahan yuridis pada saat ini. Yang dikaji dan di analisis terbatas pada 7 (tuju)  UU Khusus di luar KUHP yang menimbulkan permasalahan juridis pada saat ini yaitu meliputi: UU No. 31/1999 jo UU 20/2001 Tentang Tindak Pidana Korupsi; UU No. 21 Tahun 2014 Tentang Panas Bumi; UU No. 14 Tahun 2008 Tentang Keterbukaan Informasi Publik; UU No. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga; UU No. 15 Tahun 2001  Tentang Merek; UU No. 14 Tahun 2001  Tentang Paten; UU No. 31 Tahun 2000 Tantang Desain Industri. Kata kunci : kebijakan, kualifikasi yuridis, perundang-undangan di luar KUHP